Paper towns - Green, John, 1977- (New York : Speak, 2009)
One month before graduating from his Central Florida high school, Quentin "Q" Jacobsen basks in the predictable boringness of his life until the beautiful and exciting Margo Roth Spiegelman, Q's neighbor and classmate, takes him on a midnight adventure and then mysteriously disappears.
Includes author's note and discussion questions.
Lexile: 850.
Accelerated Reader AR
Keywords: Missing persons -- Fiction; Detective and mystery stories; Bildungsromans; High school seniors -- Fiction; Revenge -- Fiction; Neighbors -- Fiction; Coming of age -- Fiction; Realistic fiction; Mystery and detective stories; Florida -- Fiction; Orlando (Fla.) -- Fiction